Suplement do kultury religijnej współczesnego Podhala - Nowina-Sroczyńska, Ewa (Zeszyty Wiejskie, 2014)
The text is more like a supplement, complementary material to the research on the Podhale religious culture. I also use another designation of the word ‘supplement’ – I treat my reflections as material updating the dynamically changing content and form of Podhale religiousness. The subjects of analysis include new shepherd celebrations, the Holy Communion of Holy Thursday, seasonal masses at cemeteries, common gatherings before a funeral, wreaths for late maidens and bachelors, new rituals of Good Friday. These customs belong to the so-called vernacular religion that puts emphasis on relations between religion and life, practice, experience and also on the local, cultural context of tradition.